Letter to Jane Tolmach from Charles Warren - Charles Warren:::::: (1976)
In a May 21, 1976 letter, Assemblyman Charles Warren expressed his support for Jane Tolmach's candidacy in the 36th Assembly District. He assured her that she had his backing and asked what kind of assistance she needed.